An electron acceptor featuring a B–N covalent bond and small singlet–triplet gap for organic solar cells. Issue 62 (14th July 2022) - Liu, Xinyuan; Pang, Shuting; Zeng, Liang; Deng, Wanyuan; Yang, Mingqun; Yuan, Xiyue; Li, Junyu; Duan, Chunhui; Huang, Fei; Cao, Yong
Abstract : BNTT2F, an electron acceptor featuring B–N covalent bond and a singlet–triplet gap of 0.20 eV is reported. The acceptor offered an efficiency of 8.30% in solar cells, suggesting the prospect of B–N covalent bond in designing photovoltaic materials. Abstract : BNTT2F, an electron acceptor featuring a B–N covalent bond and singlet–triplet gap as low as 0.20 eV via the multiple resonance effect, is developed for organic solar cells. The optimized device based on BNTT2F offered an efficiency of 8.3%, suggesting the great prospect of B–N covalent bond-containing π-conjugated molecules for photovoltaics.